‘Ndrangheta and Mafia-enterprise in Mantova. The consequences on the local economy (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
This research aims to analyze the spread of Mafia phenomenon in Mantova and its impact on the local economic system. The main goals are to define quantitative indicators able to grasp the extent of mafia penetration in the territory and to properly demonstrate the negative consequences of this presence on the local economy. Initially is outlined the historical development of ‘ndrangheta clans settlement, giving particular attention to the current organizational structure, then is investigated how this infiltration upsets local economic framework. In order to understand the pivotal function that mafia entrepreneurship plays in the colonization strategy, performed by Grande Aracri clan, a theoretical interpretative key is provided. Finally, the hypothesis that claims mafia entrepreneurship negatively affect Mantova economy is statistically demonstrated by an OLS model.Keywords: 'ndrangheta, Mantova, Colonization, mafia entrepreneurship, economy